(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Acetic acid (Acidum aceticum) CH3–COOH has been known as "vinegar" since ancient times, its composition was discovered by the Swedish chemist Berselius in 1814. From Wikipedia, the free CH3COOH encyclopediaThe manufacturing process of producing acetic acid consists of the following stages: